2014
DOI: 10.5901/mjss.2014.v5n14p84
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between SMEs and Insurance providers in Nelson Mandela Metropolitan Area, South Africa

Abstract: Media reports on the effects of climate change on Small Medium Enterprises (SMEs) in South Africa has increased over the past decade. The amount of loss in terms of assets and infrastructure suffered by SMEs is disturbing. Yet insurance providers are not eager to insure SMEs and prefer to deal larger organisations. An empirical study of 203 SMEs was done, structured questionnaires were administered to SME owners. Data was analysed and the results illustrated factors such as the reliability of an insurer, staff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 8 publications
2
18
0
Order By: Relevance
“…For instance, expensive premiums, difficulty in understanding insurance contracts and making claims, not offering bespoke insurance services, beliefs in God and other informal coping mechanisms such as savings (susu) and reliance on friends and family were found as inhibitors. The study supports Chodokufa and Chiliya (2014) and NIC (2018) who report that SMTHEs do not have the wherewithal to cope with high premiums. An important contribution to the current literature is the finding that structural factors, which are service scheme related factors, are the main constraints to insurance uptake by SMTHEs in Ghana.…”
Section: Theoretical Contributionssupporting
confidence: 85%
See 1 more Smart Citation
“…For instance, expensive premiums, difficulty in understanding insurance contracts and making claims, not offering bespoke insurance services, beliefs in God and other informal coping mechanisms such as savings (susu) and reliance on friends and family were found as inhibitors. The study supports Chodokufa and Chiliya (2014) and NIC (2018) who report that SMTHEs do not have the wherewithal to cope with high premiums. An important contribution to the current literature is the finding that structural factors, which are service scheme related factors, are the main constraints to insurance uptake by SMTHEs in Ghana.…”
Section: Theoretical Contributionssupporting
confidence: 85%
“…This conviction is because of the bureaucratic processes applied when losses occurposing challenges when making claims. Furthermore, while some think that insurance is not needed since God will protect them from calamities (Chodokufa & Chiliya, 2014), others also indicate that insurance companies do not offer the kind of policies they need (Banerjee et al, 2014).…”
Section: Perceived Benefits and Constraints As Determinants Of Uptakementioning
confidence: 99%
“…In addition, most SMEs in South Africa do not have insurance policies to protect their assets, both fixed and current. Chodokufa (2009) found that almost half of SMEs in South Africa do not have any insurance cover in the event of a crime. A high crime rate also reduces the value of properties that are used to collaterise loans.…”
Section: Crimementioning
confidence: 99%
“…The required data for the same was collected from Sigma Explorer published by Swiss Re.VI. RESEARCH METHODOLOGYThe nature of the data is Time Series covering a span of 1991 -2015, i.e 25. years.…”
mentioning
confidence: 99%